Circulating CXCL10 in cirrhotic portal hypertension might reflect systemic inflammation and predict ACLF and mortality. (6th November 2017) - Lehmann, Jennifer M.; Claus, Karina; Jansen, Christian; Pohlmann, Alessandra; Schierwagen, Robert; Meyer, Carsten; Thomas, Daniel; Manekeller, Steffen; Claria, Joan; Strassburg, Christian P.; Trautwein, Christian; Wasmuth, Hermann E.; et al.
Abstract: Background & Aims: CXCR% ligands play an important role in hepatic injury, inflammation and fibrosis. While CXCL9 and CXCL11 are associated with survival in patients receiving transjugular intrahepatic portosystemic shunt (TIPS), the role of CXCL10 in severe portal hypertension remains unknown. Methods: A total of 89 cirrhotic patients were analysed. CXCL10 protein levels were measured in portal and hepatic blood at TIPS insertion and 2 weeks later in 24 patients. CXCL10 and IL8 levels were assessed in portal, hepatic, cubital vein and right atrium blood in a further 25 patients at TIPS insertion. Furthermore, real‐time PCR determined hepatic CXCL10‐mRNA in 40 cirrhotic patients. Results: Hepatic CXCL10 showed no association with decompensation. By contrast, circulating CXCL10‐levels were higher in portal than in hepatic vein blood, suggesting an extrahepatic source of CXCL10 in cirrhosis. However, CXCL10 protein in blood samples from portal, hepatic, cubital veins and right atrium correlated excellently with each other and with IL‐8 levels. Higher CXCL10 circulating levels were associated with presence of ascites and higher Child scores. Higher CXCL10 circulating protein levels were associated with acute decompensation, acute‐on‐chronic liver failure (ACLF) and independently with mortality. Moreover, a decrease in CXCL10 protein levels after TIPS insertion was associated with better survival in each cohort and analysed together. Discussion: Circulating CXCL10 possibly reflects systemic inflammation and it is correlated with acute decompensation, ACLF and complications in patients with severe portal hypertension receiving TIPS. CXCL10 predicts survival in these patients and a decrease in CXCL10 after TIPS may be considered a good prognostic factor.